E-Commerce of Agricultural Product Selling Using Android App - Venkatesh, P.; G, Prasath; G, Omprasanth; S, Parthipan (European Journal of Life Safety and Stability (2660-9630), 2022)
In our daily existence, we eat food, and our perseverance relies mainly upon food. A great deal of our food comes from farms and various means also. These farmers deal with their hard responsibilities regarding creating and serving many lives the country over, which pays for their sort of income. In any case, due to intermediates in the selling of their final products, the farmers can't make an increase and generally live poor. Through this endeavor, we will really need to communicate farmers directly to the client so that quick overseeing of things can be accomplished. This will achieve a basic reduction in the expenses of the things right now open in the market as well as the advantage will directly show up at the farmers' pocket. The purchaser can look for the item by its name. If the purchaser has any desire to purchase the item, he/she can add it. Likewise, the purchaser can choose the amount of an item. Likewise, the purchaser can transfer his prerequisites in regards to the items, and furthermore necessities of the item rundown will be shipped off the rancher with the assistance of GCM correspondence. We are encircled by innovation, yet many individuals are as yet uninformed about the advantages of this innovation or its utilization; with the assistance of this undertaking and the help for the consciousness of the ventures, numerous ranchers will actually want to involve it as well as will be shown how to utilize this application with its advantages.